2012
DOI: 10.1089/ast.2011.0694
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metagenomics of Two Microbial Mats at Cuatro Ciénegas Basin I: Ancient Lessons on How to Cope with an Environment Under Severe Nutrient Stress

Abstract: The Cuatro Ciénegas Basin (CCB) is an oasis in the desert of Mexico characterized by low phosphorus availability and by its great diversity of microbial mats. We compared the metagenomes of two aquatic microbial mats from the CCB with different nutrient limitations. We observed that the red mat was P-limited and dominated by Pseudomonas, while the green mat was N-limited and had higher species richness, with Proteobacteria and Cyanobacteria as the most abundant phyla. From their gene content, we deduced that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 63 publications
(84 reference statements)
5
66
0
Order By: Relevance
“…However, Braker et al (2000) screened 46 clones from marine sediment samples of the North Pacific by using restriction fragment length polymorphism and found that the frequency of restriction patterns for nirK and nirS were also equally distributed. Our evidence, along with the molecular evidence from microbialite metagenomics (Bonilla-Rosso et al, 2012 in this issue; Peimbert et al, 2012 in this issue) and comparative genomics (Moreno-Letelier et al, 2012 in this issue), points toward an ancient marine ecology (Souza et al, 2006 in this issue).…”
mentioning
confidence: 58%
“…However, Braker et al (2000) screened 46 clones from marine sediment samples of the North Pacific by using restriction fragment length polymorphism and found that the frequency of restriction patterns for nirK and nirS were also equally distributed. Our evidence, along with the molecular evidence from microbialite metagenomics (Bonilla-Rosso et al, 2012 in this issue; Peimbert et al, 2012 in this issue) and comparative genomics (Moreno-Letelier et al, 2012 in this issue), points toward an ancient marine ecology (Souza et al, 2006 in this issue).…”
mentioning
confidence: 58%
“…Comparisons were made using SEED subsystems with the following parameters: minimum E value of 10 −5 and minimum identity of 60 %. The following publically available datasets were used in this analysis (citation and MG-RAST IDs given): thrombolitic mat replicates (this study); non-lithifying (Type 1) and lithifying (Type 3) Highborne Cay stromatolitic mats (Khodadad and Foster 2012;4449590.3, 4449591.3), Cuatro Ciénegas lithifying oncolites (layered spherical microbialites) and thrombolites (Breitbart et al 2009;44440060.4, 4440067.3), Cuatro Ciénegas non-lithifying mats (Peimbert et al 2012;4442466.3, 4441363.3), Guerrero Negro hypersaline mats (Kunin et al 2008;4440964.3-4440972.3), Octopus Springs mat, Yellowstone National Park (Bhaya et al 2007;4443749.3), and a Global Ocean Sampling Sargasso Sea water column sample served as an outgroup (Rusch et al 2007;4441570.3). Multivariate analysis of the metagenomes functional subsystems was performed within the R statistical program (R Development Core Team 2010) using the random forest (version 4.6-2; Liaw and Weiner 2002) and bpca (version 1.0-10; Faria and Demetrio 2008) as previously described (Dinsdale et al 2013).…”
Section: Comparison Of Thrombolite Metagenome To Other Microbial Mat mentioning
confidence: 99%
“…Metagenomic data show that the microbialites at the CCB are not only highly divergent from each other but also very diverse taxonomically and functionally (Breitbart et al, 2009;Peimbert et al, 2012;Bonilla-Rosso et al, personal communications). This type of diverse gene composition is not common in the modern world (Rusch et al, 2007).…”
Section: The Ccb As a Model For Understanding Evolutionary Trajectorymentioning
confidence: 99%
“…As discussed above, this imposes severe P limitation, which results in biomass atomic C:P ratios that can be as high as 15,000 in the valley microbial communities (Elser et al, 2005a;Peimbert et al, 2012). Indeed, the laminated microbialites of the CCB appear to be very sensitive to the supply of phosphate; enrichment with P causes large increases in the abundance of eukaryotic diatoms (Elser et al, 2005a), which are generally present at low abundances in unfertilized CCB communities.…”
Section: The Ccb As a Model For Understanding Nutrient Limitation Effmentioning
confidence: 99%